Family Green Financial Education Based on Local Wisdom: Exploring the Values of Coastal Communities’ Local Wisdom in Promoting Green Financial Literacy - Kurniadi Romi; Dwijayanti Novia Sri; Sari Nurmala (E3S Web of Conferences)
Environmental awareness is increasingly becoming a critical global issue, as ecosystem degradation and resource depletion continue to intensify. Green finance, with its environmental, social, and economic impacts, has emerged as an innovative approach to mitigating the environmental crisis through sustainable funding. However, green family financial education, particularly one rooted in local wisdom, remains underexplored. This study aims to explore the potential of coastal communities’ local wisdom in shaping green family financial education. Using a qualitative ethnographic approach, this research involves Malay Jambi families living along the Batang Hari River as participants. Data were collected through in-depth interviews and analyzed using reflexive thematic analysis. The findings reveal that the coastal communities of the Batang Hari River integrate local wisdom into their financial and resource management, prioritizing long-term security and sustainability. They view saving and asset ownership as essential for future stability and employ eco-friendly practices such as using durable goods, organic fertilizers, and sustainable fishing methods. This commitment extends to natural resource management, where they follow ecological principles, passing down sustainable practices like responsible agricultural methods and careful use of materials in the rattan handicraft industry. These actions ensure their economic activities align with sustainability and environmental preservation, fostering both economic well-being and environmental stewardship.